The intersection of influenza infection and autoimmunity - Xie, Shunyu; Wei, Jintian; Wang, Xiaohui (Frontiers in Immunology, 2025)
The relationship between viral infection and autoimmune manifestations has been emerging as a significant focus of study, underscoring the intricate interplay between viral infections and the immune system. Influenza infection can result in a spectrum of clinical outcomes, ranging from mild illness to severe disease, including mortality. Annual influenza vaccination remains the most effective strategy for preventing infection and its associated complications. The complications arising from acute influenza infection are attributable not only to the direct effects of the viral infection but also to the dysregulated immune response it elicits. Notably, associations between influenza and various autoimmune diseases, such as Guillain-Barré Syndrome (GBS), Type 1 Diabetes (T1D), and antiphospholipid syndrome, have been reported. While viral infections have long been recognized as potential triggers of autoimmunity, the underlying mechanisms remain to be elucidated. Here, we described the pathophysiology caused by influenza infection and the influenza-associated autoimmune manifestations. Current advances on the understanding of the underlying immune mechanisms that lead to the potential strategies were also summarized.